Reflections on the Musical Mind : An Evolutionary Perspective - Schulkin, Jay (Book collections on Project MUSE., 2013)
What's so special about music? We experience it internally, yet at the same time it is highly social. Music engages our cognitive/affective and sensory systems. We use music to communicate with one another--and even with other species--the things that we cannot express through language. Music is both ancient and ever evolving. Without music, our world is missing something essential. In Reflections on the Musical Mind, Jay Schulkin offers a social and behavioral neuroscientific explanation of why music matters. His aim is not to provide a grand, unifying theory.